Mecz bokserski : S.K.S. "Czytelnik" Gdynia - Z.K.S. "Budowlani" Gdańsk". (Gdynia : [s.n.], 1947)
Afisz inform. o meczu, który miał miejsce w sali "Domu Kolejarza" w Gdyni 1.03.1947 r.
Keywords: Boks -- Polska -- Gdynia -- 1945-1970 -- druki ulotne; Boks -- Polska -- Gdynia -- 1945-1970 -- źródła; Boks -- Polska -- Gdynia -- 1945-1970 -- plakaty